Lymphatic Venous Anastomosis Can Release the Lymphedema-Associated Pain of Upper Limb after Breast Cancer Treatment - Mihara, Makoto; Hara, Hisako; Zhou, Han Peng; Tange, Shuichi; Kikuchi, Kazuki; Kawakami, Yoshihisa (Journal of Reconstructive Microsurgery Open, 2018)
Background Sometimes, chronic pain in the arm or chest could occur in postmastectomy patients. Although the pathology of the pain is unclear, the involvement of neurological mechanism, cicatricial contracture, or lymphedema is considered. The purpose of this study was to investigate the effectiveness of lymphaticovenous anastomosis (LVA) in reducing chronic pain in upper limb lymphedema patients.Patients and Methods This prospective study included consecutive 13 patients with upper limb lymphedema who received LVA. Preoperative lymphoscintigraphy and indocyanine green lymphography were performed. Pre- and postoperative pain scale were recorded using the visual analog scale (VAS). The number of cellulitis 1 year before and after LVA were compared. LVA was performed under local anesthesia, using a surgical microscope, and 12–0 nylon suture was used in the anastomosis.Results Two out of 13 patients were excluded from this study, and 11 patients were subjected to this study. All subjects were females with an average age of 64.3 years. The average lymphedema duration was 76.7 months. The average number of LVA sites was 5.7 per limb and the average follow-up period was 10.6 months. The average pre- and postoperative VAS scores were 3.5 and 0.59, respectively; the significant decrease was observed (p = 0.017). Three of the patients who had experienced cellulitis (once, twice, and four times, respectively) did not develop any cellulitis after LVA.Conclusion LVA was shown to be an effective surgical remedy for treating the lymphedema-associated pain of upper limb after breast cancer treatment.
Keywords: lymphedema; visual analog scale; lymphaticovenous anastomosis